A porous self-healing hydrogel with an island-bridge structure for strain and pressure sensors. Issue 3 (11th December 2020) - Zhang, Yue; Ren, Erhui; Li, Ang; Cui, Ce; Guo, Ronghui; Tang, Hong; Xiao, Hongyan; Zhou, Mi; Qin, Wenfeng; Wang, Xinyuan; Liu, Li
Abstract : Preparation process of PVA/CNTs/graphene hydrogel. Abstract : Conductive hydrogels have attracted widespread attention in wearable electronic devices and human motion detection. However, designing self-healing hydrogels with high conductivity and excellent mechanical properties remains a challenge. In this work, polyvinyl alcohol/carbon nanotubes/graphene (PVA/CNTs/graphene) with an island-bridge hydrogel structure and self-healing properties was designed by merging PVA/CNTs hydrogel and PVA/graphene hydrogel, in which the PVA/graphene hydrogel acts as an "island" and PVA/CNTs hydrogel acts as a "bridge" to bridge the entire conductive network. Hydrogen-bonding between the borate ion and the –OH group of PVA allows the conductive hydrogel to heal without any external stimulation. The PVA/CNTs/graphene hydrogel can be used for both stretchable strain and pressure sensors. The obtained PVA/CNTs/graphene composite hydrogel exhibits excellent electrical conductivity, extreme high elastic strain (up to 900%) and strong mechanical pressure (up to 10 kPa). The strain sensor based on the PVA/CNTs/graphene hydrogel exhibits excellent tensile strain sensitivity (a gauge factor of 152.6 in the strain region of 316–600%) and wide detection working range (1–600%) with high durability and repeatability. The sensor also remains highly sensitive when being used as a pressure sensor (−0.127 kPa −1 at 0–5 kPa). Additionally, the PVA/CNTs/graphene hydrogel-based sensor can detect human motions after multiple cuts and self-healing with excellent stability and repeatability. The PVA/CNTs/graphene hydrogel provides a new idea in the development of wearable electronics, demonstrating the potential of the next generation of wearable electronics.